2018
DOI: 10.4314/as.v16i1.2
|View full text |Cite
|
Sign up to set email alerts
|

Modelling relationship between rainfall variability and millet (<i>Pennisetum americanum</i> L.) and sorghum (<i>Sorghum bicolor</i> L. Moench.) yields in the Sudan savanna ecological zone of Nigeria

Abstract: This study models the relationship between rainfall variability parameters and millet (Pennisetum americanum L.) and sorghum (Sorghum bicolor L. Moench.) yields in the Sudan Savanna ecological zone of Nigeria. Daily rainfall data recorded by the nearby stations for the period between 1981 and 2010 as well as millet and sorghum yield data were used as inputs in the model. It attempts to develop model for predicting millet and sorghum yields based on rainfall variables. The analytical tools used in developing an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…(Tunde, 2011), this areal most similar finding with that of (Sokoto et al, 2016). Standardization of the coefficient is usually done to answer the question of which of the independent variables have a greater effects/impacts on the dependent variable in a multiple regression analysis, when the variables are measured in different units of measurement, (Mcculloch, 2008).This is also supported by the findings of (Govinda, 2013;Sokoto et al, 2016;Ram, 2016;Samuel, 2016;Haruna et al, 2017) also found a strong impact of independents variables on millet. It also indicated that independents variables have moderate impacts on Maize yield in the study area.…”
Section: Crop Yields Trend From 1997 To 2017mentioning
confidence: 66%
“…(Tunde, 2011), this areal most similar finding with that of (Sokoto et al, 2016). Standardization of the coefficient is usually done to answer the question of which of the independent variables have a greater effects/impacts on the dependent variable in a multiple regression analysis, when the variables are measured in different units of measurement, (Mcculloch, 2008).This is also supported by the findings of (Govinda, 2013;Sokoto et al, 2016;Ram, 2016;Samuel, 2016;Haruna et al, 2017) also found a strong impact of independents variables on millet. It also indicated that independents variables have moderate impacts on Maize yield in the study area.…”
Section: Crop Yields Trend From 1997 To 2017mentioning
confidence: 66%
“…Rainfall also a has a strong relation maize yield [20] and rainfall variability parameters could be used to develop yield forecast models for millet and sorghum in the Sudan Savanna zone of Nigeria [21]. To predict the response of recovery percentage against rainfall, regression graph was made (Fig.…”
Section: Relationship Between Recovery Percentage and Rainfall (Mm)mentioning
confidence: 99%
“…Value was 0.000146 (Table 5) which was significant at p<0.05, hence, the null hypothesis (Ho) was rejected, can be explained ainfall (mm) had statistically significant relation on recovery percentage. The R Square (Table 6), that means 88.76% can be explained by also a has a strong relation maize yield [20] and rainfall variability parameters could be used to develop yield forecast models for millet and sorghum in the Sudan Savanna ecological zone of Nigeria [21]. To predict the response of recovery percentage against rainfall, the linear regression graph was made (Fig.…”
mentioning
confidence: 99%